Effectiveness of common ratio analysis on the profitability of stock market investors as basis in preceding stock proces movement - Castroverde, Ann Maxyne, Garde, Crisna Erica, Luizon, Julia Isabel, Nicado, Catherine Mae, Ortaleza, Aaliyah Shakira, Relator, Danica. 4 0 16; 5 (2023)
Abstract This study entitled, Effectiveness of Common Ratio on the profitability of stock market investors as basis in predicting stock prices movement is prepared by Ann Maxyne Castroverde, Crisna Erica Garde, Julia Isabel Luizon, Catherine Mae Nicdao, Aaliyah Ortaleza and Danica Relator, in partial fulfillment of the requirements for the subject Business Research. The study was prepared under the supervision of Dr. Marivic F. Flores. This 100-page study seeks to determine whether common ratio analysis is an effective tool in improving the performance of stock market investors throughout their trading careers. This study also seeks to determine the influence of the factors: Gender, Years of Trading, Trading Style, and Profit in terms of T-Test and ANOVA. Specifically, the study aims to provide information about the factors influencing trading performance to help stock market investors be profitable in the stock market. The study sought to address the demographic profile of the investors, as well as other factors to see how it influences the investor's analysis using common ratios. This study ought to determine whether there is a significant relationship between the demographics and the factors influencing the effectiveness of common ratio analysis. The researchers have used descriptive type of research, that involves gathering data using online survey questionnaires, specifically Google Forms. There were 40 stock market investors who served as respondents for this study. The data were analyzed using the frequency, percentage, ranking, average weighted mean, T-test, and ANOVA. Based on the findings, it was discovered that common ratio analysis is an effective tool to be used as basis in predicting stock market prices movement. However, it was also discovered that people who use common ratio analysis are dealing with its limitations such as its availability to the public and how other fundamental factors are much easier to understand than them. The researchers have observed, based on the results, that most of the stock market investors are male, trading for 1 to 5 years, are position traders, and most of them earns 0 -50,000 pesos throughout their trading careers. Additionally, the factors of gender, years of trading, and amount of profit were discovered to be non-influential with the effectiveness of common ratio analysis. This means that regardless of the respondent's gender, years of trading, and profit, they still consider common ratio analysis as an effective tool in predicting stock market prices, as the general weighted mean shows. It is also found that having different trading styles has a significant difference on how they perceive the effectiveness of common ratio analysis in their trading journey. This study has ascertained that the effectiveness of common ratio analysis is reliant on what kind of trader they are. Based on the study's findings, the researchers recommend the finance educators to help those people who want to try stock market investing by building their knowledge base by analyzing fundamental factors such as common ratio analysis for it will help improve their performance. They also recommend the stock market investors to consider using common ratio analysis as one of their bases in predicting stock market price movements. They also recommend the school administrators to help students, specifically those who are taking any course related to finance, by conducting seminars relating to stock market investing so that they can build their knowledge base about the subject. Lastly, the researchers recommend to the future researchers to conduct a study, digging deeper about how highly profitable investors differ from those who earn less, with regards to their interpretation of fundamental analysis. This will help retail investors increase their chances of winning by taking trades with the right justification.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2